PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KELOM SHENY DI KOTA TASIKMALAYA - Depy Muhamad Pauzy; Gian Riksa Wibawa (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
This study aims to determine how the effect of price on the decision to purchase Kelom Sheny products in the City of Tasikmalaya. This research is descriptive and empirical. Descriptive research was conducted to obtain an overview of prices and purchasing decisions. While empirical research was conducted to determine the relationship between variables through statistical calculations. The technique of collecting data is by distributing questionnaires to 100 respondents randomly (randomly). The objects in this study are all consumers who are around the City of Tasikmalaya. The study used a survey method with a sampling technique using simple random sampling technique. The research data will be analyzed using simple linear regression, and the results of the discussion show that the price variable has a significant effect on purchasing decisions.